A Valid and Reliable Scale Development for Measuring HR Strategies of Start-ups. Issue 4 (December 2021) - Juneja, Divya; Matharu, Sukhjeet Kaur
Smaller and new businesses have different approaches to handle employees as compared to big and established organisations. The same goes for startups as well. The study aimed to create a valid and reliable scale that can be used to measure the HR strategies of the startups. The scale development involved four stages majorly. It started with content validity. The second stage was to evaluate Exploratory Factor Analysis to identify the initial structure of the scale framework. The next stage was to measure the Confirmatory Factor Analysis (CFA). Smart PLS 3.3 was used to measure the CFA. The last stage was to find the correlation between the item values. The final scale consists of 5 dimensions, namely induction HR strategy, performance appraisal and feedback HR strategy, employee engagement HR strategy, employee welfare HR strategy, and HR strategic fit. A total of 23 items were derived for measuring the construct. The derived scale will help the researcher to measure the HR Strategies in the Indian setting.